INCIDENCE OF ASPERGILLUS FLAVUS IN THE AEROSPHERE OF MAIZE FIELDS AT BHAGALPUR - A. K. CHOUDHARY, K. S. BILGRAMI AND (Indian Phytopathology, 2002)
Incidence of toxigenic and non-toxigenic strains of A. flavus in the aerosphere of maize fields growing in two different localities was carried out during 1987. On the basis of statistical analysis, it was concluded that the percentage relative density (R.D.) of A. flavus was maximum (63 per cent) during the monsoon period followed by summer (45 per cent) and winter (24 per cent). Analysis of variance showed a significant relationship between season x location. Incidence was much higher in locality B (flood affected areas of diara land) than locality A (nondiara area). Other variables like maximum and minimum temperatures, maximum and minimum RH and rainfall also influenced the distribution of A. flavus conidia/propagules. Minimum temperature coupled with maximum RH lead to high incidence of A. flavus in both the localities. The incidence of toxigenic strains of A. flavus in the aerosphere ranged from 33 to 54 per cent with the toxigenic potency for aflatoxin B1 in a range of 0.02 to 3 Âµg/ml.